Ultrasonic and clinical risk factors of solitary Plaque-RADS-2 carotid plaque for predicting anterior circulation ischemic stroke - Zhao, Shuangshuang; Zhang, Zheng; Wu, Xincai; Chen, Yanwei; Cai, Yun; Zhao, Huajiao; Bao, Jiayan; Li, Wenjun; Qian, Jiwen; Zhang, Xin; Chen, Baoding (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPlaque-RADS-2 carotid plaque is regarded as a low risk for attribution of cerebrovascular events. Nevertheless, in individuals with carotid plaque, the risk of ischemic stroke poses a continuous threat to both health and quality of life. This study aimed to investigate risk predictors of anterior circulation ischemic stroke (ACIS) in patients with solitary Plaque-RADS-2 carotid plaque.MethodsMedical records of 1,961 patients were collected at our hospital from January to December 2022. Patients with solitary Plaque-RADS-2 carotid plaque were divided into ACIS and non-ACIS groups based on brain CT/MRI results. Ultrasonic and clinical characteristics were assessed by univariate and multivariate analysis.ResultsA total of 134 patients with solitary Plaque-RADS-2 carotid plaque were enrolled in this study. Systolic blood pressure (SBP) >141.5 mmHg, glycosylated hemoglobin (HbA1c) > 7.05%, triglyceride glucose (TyG) index > 7.18, and mainly hypoechoic significantly were predictive factors for ACIS. The prediction equation was logit (P) = 2.087 × (if SBP > 141.5 mmHg) + 2.126 × (if HbA1c > 7.05%) + 1.225 × (if TyG index > 7.18) + 1.554 × (if mainly hypoechoic) − 1.795. The area under curve of receiver operating characteristic curve was 0.843.ConclusionThis study demonstrated that SBP > 141.5 mmHg, HbA1c > 7.05%, TyG index > 7.18, and mainly hypoechoic were independent predictors of ACIS in patients with solitary Plaque-RADS-2 carotid plaque. Significant attention should be given to these risk factors to improve the management of solitary Plaque-RADS-2 carotid plaque.